Analisis Tanggung Jawab Syahbandar dalam Pelayaran pada Kantor Kesyahbandaran dan Otoritas Pelabuhan - Jasruddin, Jasruddin; Putra, Zulfikar; Butuni, Syarif (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
The purpose of this study was to determine the responsibility of the harbormaster in shipping. This study used an empirical juridical approach. The responsibility of the class II Kendari Harbormaster was very important because of security and safety for matters related to shipping. The harbormaster in his duties had to ensure the awareness of sea transportation service users and had the authority to impose sanctions.